Heavy metals (Pb, Cd, As) content in instant noodles from Malaysian market - Shamsani, Nur Sabrina; Mohd Elias, Saliza; Yunus, Farhanah Hanani; Abdullah Aziz, Nurhasanah (Fakulti Perubatan dan Sains Kesihatan, Universiti Putra Malaysia, 2019)
Instant noodles had been found to be contaminated with heavy metals such as lead (Pb), cadmium (Cd) and arsenic (As). This study aims to determine the heavy metals (Pb, Cd, As) concentration in popular instant noodles from Malaysian market. Seven different brands of commercially popular instant noodles were randomly sampled from the market. The samples were prepared by dry ashing method prior to analysis by using Inductively Coupled Plasma Mass Spectrophotometer (ICP-MS). Results showed that all seven samples detected with heavy metals which the concentration for Pb in two samples exceeded the maximum permitted level of Malaysian Food Act and Regulation of 2 mg/kg. This finding indicated that instant noodle can be one the sources of chronic exposure to toxic heavy metals through food consumption which later might cause health effects. Instant noodles in Malaysian market need to be closely monitored to ensure the food quality and safety for consumption. Further study which focuses on the source of contamination as well as the health risk of consuming this contaminated noodles is strongly recommended.